Root cause analysis strategy for robust design domain recognition. Issue 8 (3rd August 2018) - Yang, Junqi; Zhan, Zhenfei; Chou, Clifford C.; Yang, Ren-Jye; Zheng, Ling; Guo, Gang
ABSTRACT: Design domain identification with desirable attributes ( e.g. feasibility, robustness and reliability) provides advantages when tackling large-scale engineering optimization problems. For the purpose of dealing with feasibility robustness design problems, this article proposes a root cause analysis (RCA) strategy to identify desirable design domains by investigating the root causes of performance indicator variation for the starting sampling initiation of evolutionary algorithms. The iterative dichotomizer 3 method using a decision tree technique is applied to identify reduced feasible design domain sets. The robustness of candidate domains is then evaluated through a probabilistic principal component analysis-based criterion. The identified robust design domains enable optimal designs to be obtained that are relatively insensitive to input variations. An analytical example and an automotive structural optimization problem are demonstrated to show the validity of the proposed RCA strategy.